Mediating Role of Islamic Social Reporting on the Nexus Between Sharia Supervisory Board Characteristics and Islamic Banks' Financial Performance in Indonesia - Chitra Yuliashri Katili; Rifadli D. Kadir; Asma Polapa; Ritfiani Gobel (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2025)
Purpose: The Sharia Supervisory Board (SSB) plays a significant role in Islamic banking. Therefore, it is important to examine how the characteristics of the SSB influence financial performance, particularly when mediated by Islamic Social Reporting (ISR).Method: This study adopts a quantitative approach. We analyze the annual financial statements of 13 Islamic commercial banks in Indonesia from 2019 to 2023, focusing on how SSB characteristics affect financial performance through ISR. Structural Equation Modelling (SEM) is used to test the proposed hypothesis, utilizing SEM-PLS with Smart-PLS 4 as the analysis tool.Result: The analysis reveals that SSB characteristics do not significantly impact financial performance, suggesting that the role of the SSB has not sufficiently influenced financial outcomes. However, SSB characteristics significantly affect ISR, which in turn has a significant impact on financial performance. The mediation analysis shows that ISR fully mediates the relationship between SSB characteristics and financial performance. Therefore, ISR is a crucial factor in improving the financial performance of Islamic banks.Practical Implications for Economic Growth and Development: This study recommends that Islamic banks enhance the role of the SSB, particularly in ensuring transparent and effective social disclosures. Strengthening ISR practices can improve financial performance, thereby increasing Islamic banking’s contribution to community financing and fostering broader economic growth.